Tangential Film Verification for Lung Volume Involvement in Breast Cancer Radiation Treatment: East Coast Malaysia Experience - Reduan, A; Mazurawati, M; Bhavaraju, VMK; Nik Ruzman, NIb; Nor Shazleen, AS (School of Health Sciences, Universiti Sains Malaysia, 2013)
Post mastectomy or lumpectomy irradiation of the chest wall or breast is common practice to minimize the local recurrences. Chest wall irradiation is a complicated technical procedure as the pathological target volume involves the normal structures like lung, heart, and head of humerus, esophagus and trachea known as organ at risk. The aim of this study was to verify the cases of the conventional tangential field technique among the breast cancer patients from year 2006 to 2011. In this study, the previous data of breast cancer patients treated with radiation from 2006 to 2011 were evaluated. Conventional 2D planning was done by taking body contour of the patient. Tangential verification films were taken in patients where excess of lung volume was suspected. The data was analyzed to verify the real lung volume irradiated. From a total 112 patients underwent tangential verification films during that period, 33% of patients underwent breast conservative surgery (BCS) while the rest underwent mastectomy. The depth of the field from the skin to 90% isodose ranges from 2.0 to 8.0 cm. However, 15 (13.4%) out 112 patients needed a replanning. As a conclusion, from 112 cases, the numbers of re-plan cases for year 2006 to 2011 were only 13 (11.61%) which is less than 15%. This result can be used by the centre who no dot have the facilities for simulation to verify the depth dose in 2D planning.